Small Force, Big Impact: Next Generation Organ-on-a-Chip Systems Incorporating Biomechanical Cues - Ergir, Ece; Bachmann, Barbara; Redl, Heinz; Forte, Giancarlo; Ertl, Peter (Frontiers in Physiology, 2018)
Mechanobiology-on-a-chip is a growing field focusing on how mechanical inputs modulate physico-chemical output in microphysiological systems. It is well known that biomechanical cues trigger a variety of molecular events and adjustment of mechanical forces is therefore essential for mimicking in vivo physiologies in organ-on-a-chip technology. Biomechanical inputs in organ-on-a-chip systems can range from variations in extracellular matrix type and stiffness and applied shear stresses to active stretch/strain or compression forces using integrated flexible membranes. The main advantages of these organ-on-a-chip systems are therefore (a) the control over spatiotemporal organization of in vivo-like tissue architectures, (b) the ability to precisely control the amount, duration and intensity of the biomechanical stimuli, and (c) the capability of monitoring in real time the effects of applied mechanical forces on cell, tissue and organ functions. Consequently, over the last decade a variety of microfluidic devices have been introduced to recreate physiological microenvironments that also account for the influence of physical forces on biological functions. In this review we present recent advances in mechanobiological lab-on-a-chip systems and report on lessons learned from these current mechanobiological models. Additionally, future developments needed to engineer next-generation physiological and pathological organ-on-a-chip models are discussed.